Perceptions of interjurisdictional competition and cooperation: A gender comparison of administrators in economic development. Issue 5 (19th October 2020) - Yaskewich, David M.
ABSTRACT: The desire to grow a tax base often compels local governments to compete and cooperate simultaneously with nearby jurisdictions. Managing interjurisdictional relations is an important role of administrative officers. While scholars have expressed concern about the dominance of masculine imagery and the underrepresentation of women in public administration, gender's role in interjurisdictional relations has received little attention. This study compared perceptions of interjurisdictional competition and cooperation among US. city and county administrators. The main results suggest that men and women have similar perceptions of competition and cooperation. Moreover, perceptions of whether competition comes from nearby or distant jurisdictions also does not appear to vary by gender. Rather than being influenced by individual identities, perceptions varied based on institutional characteristics, such as the extent of local responsibility over economic development planning, the number of organizations that participate in the planning process, and fiscal decentralization.